2017
DOI: 10.1016/j.jallcom.2017.04.065
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of lithium ion in anatase TiO 2 nanotube arrays of different morphology

Abstract: Anatase TiO 2 nanotube arrays of different morphology were prepared by a two-step process: anodic oxidation at voltages 20-60V and subsequent annealing at 400 o C. By amplifying anodization voltage the inner diameter of nanotubes increased. At 60V nanotubes changed the shape from cylindrical tube to truncated cone with elliptical opening. Electrochemical insertion of Li-ion in nanotubes was studied by cyclic voltammetry and galvanostatic charge-discharge experiments. The cyclovoltammetric response was fast for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 35 publications
(53 reference statements)
2
16
0
Order By: Relevance
“…At the lowest scan rate of 1 mV•s −1 (Fig. 4b), redox peak-to-peak separation is 0.441 V and is similar to that observed for IL-based electrolytes [19,20], and also for LiPF 6 /EC-DMC [79] and LiClO 4 /PC [80] electrolyte. Figure 4b demonstrates the influence of temperature on CVs recorded at a scan rate 5 mV•s −1 .…”
Section: Cyclic Voltammetrysupporting
confidence: 79%
“…At the lowest scan rate of 1 mV•s −1 (Fig. 4b), redox peak-to-peak separation is 0.441 V and is similar to that observed for IL-based electrolytes [19,20], and also for LiPF 6 /EC-DMC [79] and LiClO 4 /PC [80] electrolyte. Figure 4b demonstrates the influence of temperature on CVs recorded at a scan rate 5 mV•s −1 .…”
Section: Cyclic Voltammetrysupporting
confidence: 79%
“…Various crystalline TiO 2 polymorphs (e.g., rutile, anatase, brookite, and bronze) have also been investigated as alternatives to LTO as a LIB anode material. Titanium dioxide has a theoretical capacity of 335 mA h g –1 or 1280 mA h cm –3 , which corresponds to the accommodation of one Li ion in one TiO 2 formula unit. Bulk crystalline TiO 2 exhibits poor ionic and electronic conductivities; therefore, it is necessary to use electrode doping strategies and/or nanoarchitectures (e.g., nanotubes, nanomembranes, nanospindles, and so forth) to increase lithiation capacity at high rates. Nanoarchitecture electrodes, such as nanotube arrays and thin films with a thickness in the order of nanometers, exhibit reduced phase segregation and reduced electrode structural change during cycling, suggesting that Li + insertion in TiO 2 is driven by a competition between the solid solution and phase segregation.…”
Section: Introductionmentioning
confidence: 99%
“…The equivalent circuit shown in Figure 3.9 was used to fit the experimentally obtained data to obtain the Li diffusivity (Table 4.3). The calculated diffusivities were comparable to values already reported in literature [105][106][107] . From the fitting, it was found that the WV-treated sample had the largest Li diffusivity.…”
Section: Eis Plotssupporting
confidence: 89%